Strong correlation between meiotic crossovers and haplotype structure in a 2.5-Mb region on the long arm of chromosome 21 - Greenawalt, Danielle M.; Cui, Xiangfeng; Wu, Yujun; Lin, Yong; Wang, Hui-Yun; Luo, Minjie; Tereshchenko, Irina V.; Hu, Guohong; Li, James Y.; Chu, Yi; Azaro, Marco A.; DeCoste, Christina J.; et al. (Genome Research, 2006)
Although the haplotype structure of the human genome has been studied in great detail, very little is known about the mechanisms underlying its formation. To investigate the role of meiotic recombination on haplotype block formation, single nucleotide polymorphisms were selected at a high density from a 2.5-Mb region of human chromosome 21. Direct analysis of meiotic recombination by high-throughput multiplex genotyping of 662 single sperm identifies 41 recombinants. The crossovers were nonrandomly distributed within 16 small areas. All, except one, of these crossovers fall in areas where the haplotype structure exhibits breakdown, displaying a strong statistically positive association between crossovers and haplotype block breaks. The data also indicate a particular clustered distribution of recombination hotspots within the region. This finding supports the hypothesis that meiotic recombination makes a primary contribution to haplotype block formation in the human genome.